Human and Porcine Marginal Chordal Forces in a Vacuum Based Physiological In Vitro Mitral Valve Model - Mads V. Ancker; Sam E. Stephens; Justin T. Jack; Neil B. Ingels; Jonathan F. Wenk; Søren N. Skov; Surendra K. Chawla; Ajit. P. Yoganathan; Morten O. Jensen (Cardiovascular Engineering and Technology, 2026)
Introduction This study aimed to quantitatively investigate the role of marginal chordae of the mitral valve during static closure by analyzing the force within these chordae and its potential correlation with the transvalvular pressure. Materials and Methods Porcine (n = 10) and human (n = 4) mitral valves were mounted in a saddle-shaped annulus clamp, while an in vitro system was utilized to replicate a physiological systolic blood pressure by vacuum pressure applied to the atrial side of the valve. A Millar pressure catheter and force transducers (“C-gauges”) were used to acquire the data. Strut chordal force was recorded simultaneously with the marginal chordal force, to serve as a verification of the employed equipment. Results The marginal chordal force in porcine and human averaged to 0.012 N ± 0.008 N and 0.006 N ± 0.008 N respectively at peak systolic pressure of 120 mmHg. Additionally, a simplified finite element study was conducted and supports low marginal forces relative to intermediary chords. Discussion & Conclusion This low force calls into question the traditionally-described role of the marginal chordae in preventing mitral prolapse at closure. The chords do, however, still show signs of assisting with the leaflets’ positioning. The relationship between marginal chordal forces and transvalvular pressure varies significantly across experiments, further obfuscating their role in normal valvular function.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Development and Characteristics of a Dual-Layered Vascular Phantom - Kaitlyn M. Elmer; Cassidy Caffin; Breeanna Scott; Sam E. Stephens; Morten O. Jensen (Cardiovascular Engineering and Technology, 2026)
Purpose Cardiovascular phantoms are used in biomedical research and development applications, allowing for complex geometries to be studied in a controlled environment. The various layers of human tissue have been difficult to mimic in these phantoms. In this study, a novel dual-layer cardiovascular phantom is created. Methods The interior lumen is 3D printed using an elastic vat-photopolymerization resin and cast within an industry standard tissue-mimicking ballistics gel. Strips of the 3D-printed resin were prepared and tested to determine Young’s modulus, Ultimate tensile strength, and elongation at break. Results The final phantoms were reproducible, semi-transparent, and suitable for microCT scanning. Additionally, the 3D-printed elastic materials had: Young’s Modulus of 12 +/- 3.2 MPa, UTS of 1.27 +/- 0.44 MPa, and elongation at break of 29 +/- 9%. These results are within the physiological ranges of human tissues. There was a moderate correlation between the thickness of the sample and stiffness, which may be important depending on the application of the models. Conclusion The methods for producing a dual-layered phantom are reproducible and appropriate for a variety of biomedical applications.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

STICr: An open-source package and workflow for stream temperature, intermittency, and conductivity (STIC) data - Sam Zipper; Christopher T. Wheeler; Delaney M. Peterson; Stephen C. Cook; Sarah E. Godsey; Ken Aho (Environmental Modelling & Software, 2025)

Building meaningful collaboration in conservation genetics and genomics - Robyn E. Shaw; Brittany Brockett; Jennifer C. Pierson; Stephen D. Sarre; Paula Doyle; Hannah B. Cliff; Mark D. B. Eldridge; Kimberly A. Miller; Kym Ottewell; Marissa L. Parrott; Maurizio Rossetto; Paul Sunnucks; et al. (Conservation Genetics, 2024)
Genetic diversity is the foundation of biodiversity, and preserving it is therefore fundamental to conservation practice. However, global conservation efforts face significant challenges integrating genetic and genomic approaches into applied management and policy. As collaborative partnerships are increasingly recognized as key components of successful conservation efforts, we explore their role and relevance in the Australian context, by engaging with key entities from across the conservation sector, including academia, botanic gardens, herbaria, seed banks, governmental/non-governmental organisations, private industry, museums, Traditional Owners, Indigenous rangers, and zoos and aquaria. By combining perspectives from these entities with comprehensive literature review, we identified five guiding principles for conservation genetic and genomic research and explored the different elements of, and approaches to, collaboration. Our reflections suggest that there is a substantial overlap in research interests across the Australian conservation sector, and our findings show that collaboration is increasing. We discuss approaches to building collaborative partnerships, the reciprocal benefits of collaborating, and some remaining challenges associated with data generation, data collection, and cross-cultural considerations. We emphasise the need for long-term national resourcing for sample and data storage and consistency in collecting, generating and reporting genetic data. While informed by the Australian experience, our goal is to support researchers and practitioners to foster meaningful collaborations that achieve measurable management outcomes in conservation genetics and genomics, both in Australia and globally.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Critical Information from High Fidelity Arterial and Venous Pressure Waveforms During Anesthesia and Hemorrhage - Lauren D. Crimmins-Pierce; Gabriel P. Bonvillain; Kaylee R. Henry; Md Abul Hayat; Adria Abella Villafranca; Sam E. Stephens; Hanna K. Jensen; Joseph A. Sanford; Jingxian Wu; Kevin W. Sexton; Morten O. Jensen (Cardiovascular Engineering and Technology, 2022)

Development of Custom Wall-Less Cardiovascular Flow Phantoms with Tissue-Mimicking Gel - Megan E. Laughlin; Sam E. Stephens; Jamie A. Hestekin; Morten O. Jensen (Cardiovascular Engineering and Technology, 2022)
Purpose Flow phantoms are used in experimental settings to aid in the simulation of blood flow. Custom geometries are available, but current phantom materials present issues with degradability and/or mimicking the mechanical properties of human tissue. In this study, a method of fabricating custom wall-less flow phantoms from a tissue-mimicking gel using 3D printed inserts is developed. Methods A 3D blood vessel geometry example of a bifurcated artery model was 3D printed in polyvinyl alcohol, embedded in tissue-mimicking gel, and subsequently dissolved to create a phantom. Uniaxial compression testing was performed to determine the Young’s moduli of the five gel types. Angle-independent, ultrasound-based imaging modalities, Vector Flow Imaging (VFI) and Blood Speckle Imaging (BSI), were utilized for flow visualization of a straight channel phantom. Results A wall-less phantom of the bifurcated artery was fabricated with minimal bubbles and continuous flow demonstrated. Additionally, flow was visualized through a straight channel phantom by VFI and BSI. The available gel types are suitable for mimicking a variety of tissue types, including cardiac tissue and blood vessels. Conclusion Custom, tissue-mimicking flow phantoms can be fabricated using the developed methodology and have potential for use in a variety of applications, including ultrasound-based imaging methods. This is the first reported use of BSI with an in vitro flow phantom.

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

The modern pollen–vegetation relationships of a tropical forest–savannah mosaic landscape, Ghana, West Africa - Adele C.M. Julier; Phillip E. Jardine; Stephen Adu-Bredu; Angela L. Coe; Akwasi Duah-Gyamfi; Wesley T. Fraser; Barry H. Lomax; Yadvinder Malhi; Sam Moore; Kennedy Owusu-Afriyie; William D. Gosling (Palynology, 2018)

Pollen-vegetation richness and diversity relationships in the tropics - William D. Gosling; Adele C. M. Julier; Stephen Adu-Bredu; Gloria D. Djagbletey; Wesley T. Fraser; Phillip E. Jardine; Barry H. Lomax; Yadvinder Malhi; Emmanuel A. Manu; Francis E. Mayle; Sam Moore (Vegetation History and Archaeobotany, 2018)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Convergence of bark investment according to fire and climate structures ecosystem vulnerability to future change - Adam F. A. Pellegrini; William R. L. Anderegg; C. E. Timothy Paine; William A. Hoffmann; Tyler Kartzinel; Sam S. Rabin; Douglas Sheil; Augusto C. Franco; Stephen W. Pacala (Ecology Letters, 2017)
Fire regimes in savannas and forests are changing over much of the world. Anticipating the impact of these changes requires understanding how plants are adapted to fire. In this study, we test whether fire imposes a broad selective force on a key fire‐tolerance trait, bark thickness, across 572 tree species distributed worldwide. We show that investment in thick bark is a pervasive adaptation in frequently burned areas across savannas and forests in both temperate and tropical regions where surface fires occur. Geographic variability in bark thickness is largely explained by annual burned area and precipitation seasonality. Combining environmental and species distribution data allowed us to assess vulnerability to future climate and fire conditions: tropical rainforests are especially vulnerable, whereas seasonal forests and savannas are more robust. The strong link between fire and bark thickness provides an avenue for assessing the vulnerability of tree communities to fire and demands inclusion in global models.

Observations of a New Zealand dolphin ( Cephalorhynchus hectori ) breathing via its mouth - Stephen M. Dawson; R. Ewan Fordyce; Sam H. Ridgway; Thomas E. Brough; Elisabeth Slooten (Marine Mammal Science, 2017)

Evaluation of terrestrial carbon cycle models for their response to climate variability and to CO 2 trends - Shilong Piao; Stephen Sitch; Philippe Ciais; Pierre Friedlingstein; Philippe Peylin; Xuhui Wang; Anders Ahlström; Alessandro Anav; Josep G. Canadell; Nan Cong; Chris Huntingford; Martin Jung; et al. (Global Change Biology, 2013)
The purpose of this study was to evaluate 10 process‐based terrestrial biosphere models that were used for the IPCC fifth Assessment Report. The simulated gross primary productivity ( GPP ) is compared with flux‐tower‐based estimates by Jung et al . [ Journal of Geophysical Research 116 (2011) G00J07] ( JU 11). The net primary productivity ( NPP ) apparent sensitivity to climate variability and atmospheric CO 2 trends is diagnosed from each model output, using statistical functions. The temperature sensitivity is compared against ecosystem field warming experiments results. The CO 2 sensitivity of NPP is compared to the results from four Free‐Air CO 2 Enrichment ( FACE ) experiments. The simulated global net biome productivity ( NBP ) is compared with the residual land sink ( RLS ) of the global carbon budget from Friedlingstein et al . [ Nature Geoscience 3 (2010) 811] ( FR 10). We found that models produce a higher GPP (133 ± 15 Pg C yr −1 ) than JU 11 (118 ± 6 Pg C yr −1 ). In response to rising atmospheric CO 2 concentration, modeled NPP increases on average by 16% (5–20%) per 100 ppm, a slightly larger apparent sensitivity of NPP to CO 2 than that measured at the FACE experiment locations (13% per 100 ppm). Global NBP differs markedly among individual models, although the mean value of 2.0 ± 0.8 Pg C yr −1 is remarkably close to the mean value of RLS (2.1 ± 1.2 Pg C yr −1 ). The interannual variability in modeled NBP is significantly correlated with that of RLS for the period 1980–2009. Both model‐to‐model and interannual variation in model GPP is larger than that in model NBP due to the strong coupling causing a positive correlation between ecosystem respiration and GPP in the model. The average linear regression slope of global NBP vs. temperature across the 10 models is −3.0 ± 1.5 Pg C yr −1 °C −1 , within the uncertainty of what derived from RLS (−3.9 ± 1.1 Pg C yr −1 °C −1 ). However, 9 of 10 models overestimate the regression slope of NBP vs. precipitation, compared with the slope of the observed RLS vs. precipitation. With most models lacking processes that control GPP and NBP in addition to CO 2 and climate, the agreement between modeled and observation‐based GPP and NBP can be fortuitous. Carbon–nitrogen interactions (only separable in one model) significantly influence the simulated response of carbon cycle to temperature and atmospheric CO 2 concentration, suggesting that nutrients limitations should be included in the next generation of terrestrial biosphere models.

In-Street Wind Direction Variability in the Vicinity of a Busy Intersection in Central London - Ahmed A. Balogun; Alison S. Tomlin; Curtis R. Wood; Janet F. Barlow; Stephen E. Belcher; Robert J. Smalley; Justin J. N. Lingard; Sam J. Arnold; Adrian Dobre; Alan G. Robins; Damien Martin; Dudley E. Shallcross (Boundary-Layer Meteorology, 2010)